1987
DOI: 10.1093/infdis/155.6.1254
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Oral Salmonella dublin Infection in BALB/c Mice: Effect of an 80-Kilobase-Pair Plasmid on Virulence

Abstract: BALB/c mice were infected orally with Salmonella dublin strains Lane and LD842, an isogenic derivative of the former that is avirulent because it was cured of its 80-kilobase-pair virulence plasmid pSDL2. Both strains colonized the intestine and invaded Peyer's patches with equivalent efficiency. However, the parent strain multiplied in mesenteric nodes and in the spleen; the plasmid-cured strain reached these organs, but the infection was low grade and remained relatively static until the mice developed activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
2
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 24 publications
2
77
2
1
Order By: Relevance
“…Furthermore, a low inoculum more accurately re¯ects the in vivo situation. Viable bacteria in the livers and spleens of infected mice increase 10 4 -to 10 5 -fold from an initial load of only a few hundred organisms after oral infection (Heffernan et al, 1987). Our results are compatible with an earlier in vivo study using a different temperature-sensitive plasmid to demonstrate that the spv genes appeared to increase the intracellular growth rate of S. typhimurium in the spleen (Gulig and Doyle, 1993).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a low inoculum more accurately re¯ects the in vivo situation. Viable bacteria in the livers and spleens of infected mice increase 10 4 -to 10 5 -fold from an initial load of only a few hundred organisms after oral infection (Heffernan et al, 1987). Our results are compatible with an earlier in vivo study using a different temperature-sensitive plasmid to demonstrate that the spv genes appeared to increase the intracellular growth rate of S. typhimurium in the spleen (Gulig and Doyle, 1993).…”
Section: Discussionsupporting
confidence: 90%
“…Dublin virulence plasmid genes (sp ) have been found to be strongly expressed when the organism is within eucaryotic cells and to be regulated by both SpvR and RpoS [135,136]. The sp genes are required for survival and replication of Dublin within bovine monocytes [131,137], and experimental Dublin infections have shown that these virulence genes are necessary for the development of systemic salmonellosis in both the bovine and murine hosts but do not affect the capability of Dublin to colonize the intestine, to invade PP or to cause diarrhoea in cattle [138,139]. Alternatively, enteric inflammation appears to be due to Dublin adhesion to the epithelial cells and is mediated by activation of the proinflammatory genes transcription factor NF-kB and chemokine (i.e.…”
Section: Dublinmentioning
confidence: 99%
“…or i.v. in a lateral tail vein in 0.1 ml PBS or orally by gavage in 0.1 ml 0.1 M NaHCO 3 (23). Mice were sacrificed at intervals, and the tissues were removed sterilely, homogenized, and then diluted in saline for quantitative cultures as previously described (23).…”
Section: Infectionmentioning
confidence: 99%